Pengaruh Employer Branding dan E-Recruitment terhadap Intention to Apply (Studi pada Program MAP GROW Batch 6) - Kezia Safanya Khairunnisa; Rofi Rofaida; Yoga Perdana (Jurnal Manajemen dan Bisnis Kreatif)
The retail industry will face systemic challenges, one of which is a labor shortage. Generation Z, with work expectations different from previous generations, presents a new challenge for companies in attracting, developing, and retaining talent. PT Mitra Adiperkasa Tbk (MAP), as a leading retail company in Indonesia, has partnered with the Kampus Merdeka program through the Magang dan Studi Independen Bersertifikat (MSIB) program since 2021 with a program called MAP GROW. This study aims to measure the influence of employer branding and e-recruitment on the intention to apply for the MAP GROW Batch 6 program. The research method used is descriptive and verificative quantitative, with data collected through questionnaires distributed to 112 applicants of the MAP GROW Batch 6 program. The sampling technique used is purposive sampling, and data analysis was conducted using correlation coefficient analysis, multiple linear regression, and coefficient of determination, as well as hypothesis testing through the F-test and t-test. The research results indicate that employer branding and e-recruitment have been effectively implemented in the MAP GROW Batch 6 program, as reflected in the high number of applicants representing the intention to apply. Additionally, both variables have a positive and significant effect on the intention to apply, both simultaneously and partially, with e-recruitment having a greater influence. These findings suggest that optimal employer branding and e-recruitment strategies can enhance the intention to apply to a company.